ANALYSIS OF THE FACTORS AFFECTING THE PREFERENCE FOR RECREATION AREAS BY MULTIDIMENSIONAL SCALING METHOD - (:unkn) unknown (SCIBULCOM LTD, 2010)
To establish rural development, there are various methods and ways. Ecotourism is one of the significant tools that are benefited in providing rural development. Ecotourism activities have spread all over Turkey in recent years. The coast of Kastro is one of the most important ecotourism areas of Thrace and the area is visited nearly 50 000 people in July and August every year. The most important factor for those visitors to choose Kastro is its high environmental quality. Another factor is that it is surrounded by forests with 2.5 lengths of coast, clean sea and the distance from inhabited areas. Additionally, being close to Istanbul and protected by special guards during summer make it an attractive place. In this study, the motivation factors affecting visitors preference for the recreation area are analysed by multidimensional scaling method. The results are significant in terms of ecotourism determining the factors affecting visitors demands for firms marketing recreational goods.
Keywords: ecotourism; multidimensional scaling; recreation areas; Kastro; visitors number